Relationship between Levels of Brain-Derived Neurotrophic Factor and Metabolic Parameters in Patients with Type 2 Diabetes Mellitus. (22nd December 2014) - Boyuk, Banu; Degirmencioglu, Serife; Atalay, Hande; Guzel, Savas; Acar, Ayse; Celebi, Aslan; Ekizoglu, Ismail; Simsek, Caglar
Abstract : Background and Aim . Studies have suggested that brain-derived neurotrophic factor (BDNF) plays a role in glucose and lipid metabolism and inflammation. The aim of this study was to evaluate the relationship between serum BDNF levels and various metabolic parameters and inflammatory markers in patients with type 2 diabetes mellitus (T2DM). Materials and Methods . The study included 88 T2DM patients and 33 healthy controls. Fasting blood samples were obtained from the patients and the control group. The serum levels of BDNF were measured with an ELISA kit. The current paper introduces a receiver-operating characteristic (ROC) generalization curve to identify cut-off for the BDNF values in type 2 diabetes patients. Results . The serum levels of BDNF were significantly higher in T2DM patients than in the healthy controls (206.81 ± 107.32 pg/mL versus 130.84 ± 59.81 pg/mL; P < 0.001 ). They showed a positive correlation with the homeostasis model assessment of insulin resistance (HOMA-IR) (r = 0.28 ; P < 0.05 ), the triglyceride level (r = 0.265 ; P < 0.05 ), and white blood cell (WBC) count (r = 0.35 ; P < 0.001 ). In logistic regression analysis, age (P < 0.05 ), body mass index (BMI) (P < 0.05 ), C-reactive protein (CRP) (P < 0.05 ), and BDNF (P < 0.01 ) were independently associated with T2DM. In ROC curve analysis, BDNF cut-off was 137. Conclusion . The serum BDNF level was higher in patients with T2DM. The BDNF had a cut-off value of 137. The findings suggest that BDNF may contribute to glucose and lipid metabolism and inflammation.